Preparatory actions and indicators for their assessment in competitive fights of highly qualified karatekas in the olympic weight category up to 67 kg - Orlov Yu.L. ,; Tian Zhiyue,; Ryzhkova L.G. ,; Orlova A.Yu. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determine the versatility, effectiveness and success of preparatory actions used in competitive fights by highly qualified karatekas for the successful implementation of offensive and defensive actions. Methods and structure of the study. Pedagogical supervision was carried out over highly qualified athletes occupying leading positions in the world rankings in the weight category up to 67 kg: Assadilov Darkhan (Kazakhstan), Dacosta Steven (France), Crescenzo Angelo (Italy), El-Sawy Ali (Egypt), as well as the leader Russian national team in this competitive discipline, Honored Master of Sports Evgeniy Plakhutin. Competitive fights at the 2020 Olympic Games, world and continental championships, where athletes achieved high results, were examined. Results and conclusions. The analysis of the competitive activity of highly qualified karatekas in the Olympic weight category up to 67 kg, who occupy leading positions in the world rankings, was carried out thanks to pedagogical observations using video recording tools, which make it possible to conduct research without interfering in the competitive activity of athletes and evaluate the actions of both opponents at once using video replays of combat fights, accurately record the technical and tactical actions used by the participants in the fight and their instant-remote characteristics. The results of a survey of the competitive activity of the strongest karatekas in the world make it possible to identify differences in the indicators of the volume of preparatory actions, their versatility, efficiency and success. It is noted that the leader of the world ranking has the highest volume of use of preparatory actions, which confirms their importance for the successful conduct of competitive struggle.